Effect of match or mismatch of maternal–offspring nutritional environment on the development of offspring in broiler chickens - E.H. van der Waaij; H. van den Brand; J.A.M. van Arendonk; B. Kemp (Animal, 2011)
In mammals, maternal food restriction around conception and during pregnancy results in low birth weight and an adjusted growth trajectory of offspring. If, subsequently, the offspring are born into a food-abundant environment, they are at increased risk of developing obesity, type 2 diabetes, hypertension and renal dysfunction. Here, we show similar effects of maternal undernutrition on hatch weight, growth and fat deposition in offspring of birds (domestic chicken). Both mothers and offspring were fed either ad libitum or restricted in a two-by-two factorial design, resulting in two matched and two mismatched maternal–offspring nutritional environments. Offspring of ad libitum mothers grew heavier than those of restricted mothers, possibly due to the larger muscle mass. Ad libitum-fed offspring, especially females, of restricted mothers were lighter at hatch, and were heavier and had more abdominal fat at 6 weeks of age than daughters of ad libitum-fed mothers. These results suggest a common mechanism in mammals and birds in response to a mismatch in the maternal–offspring nutritional environment. They also indicate that the common practice of restrictive feeding of the broiler breeders and subsequent ad libitum feeding of the broilers may result in reduced growth and increased abdominal fat as compared to broilers of less restricted broiler breeders.